The importance of applying modern trends in accounting education and qualification in accordance with international accounting education standards in enhancing the quality of accounting outputs Case study Algeria - Tunisia - Morocco - Bensaleh, Abdelallah; Mohamed, ratoul (Dirassat Journal Economic Issue, 2016)
This research is based on a proposed conception of application of standards accounting education and its role in quality control of accounting curricula in Algeria, Tunisia and morocco. The rationale behind the study was the in adherence to international standards when designing accounting courses at universities, which fact that negatively affects the quality of accounting and is reflected in neglect of training aspects during study. Hence, this research aims to shed light on international education accounting and how it can be utilized when designing accounting courses within universities. The secondary goals include study and analysis of standards of accounting education and how they can be made use of in designing accounting courses, as well as drawing a framework that can guide in designing and evaluating these courses.